E-Learning as Part of Disaster Recovery Planning - Hanssen, Graeme M.; Rana, Tohid Ahmed (2007)
The world has recently witnessed large natural disasters with the Asian tsunami, the Pakistan earthquake, etc, which has resulted in loss of life measured in hundreds of thousands. One or two years later surveys of reconstruction work have revealed less than 25% of schools have been re-established, implicating long term economic and social consequences. Disaster Recovery planning could include rapid deployment of E-learning systems adapted to disaster zones, even with an apparent lack of broadband telecommunications infrastructure. This paper proposes technically innovative solutions to the rapid re-starting of education in disaster-struck communities by introducing the concept of a mobile E-school. Planning for Disaster Recovery could include the solutions proposed herein, as it is also possible to imagine in this Globalization World that budgets of wealthier nations encompassing these concepts. (Contains 1 figure.)
Publication Title: Online Submission KerkoCite.ItemAlsoKnownAs: 2339240:TNQWGH3K 2405685:7VPDA68G
Keywords: Computer Uses in Education; Distance Education; Educational Technology; Emergency Programs; Foreign Countries; Global Approach; Natural Disasters; Online Courses; Telecommunications; Virtual Classrooms